Hubungan Status Pekerjaan Ibu dan Dukungan Suami terhadap Pemberian ASIEksklusif - Ilham Fahrudin; Devi Usdiana Rosyidah; Burhanuddin Ichsan; Tri Agustina (Herb-Medicine Journal: Terbitan Berkala Ilmiah Herbal, Kedokteran dan Kesehatan, 2020)
Breast milk is the best source of nutrition to be given to newborn babies specifically designed to meet all thenutritional needs of a baby during the first six months of life. Many factors affect exclusive breastfeeding includingthe  mother'semploymentstatusand husband's support. This study aims to analyze the relationship between mother'semployment status and husband's support with exclusive breastfeeding.Thisstudyuses a cross sectional approach.Interviews were conducted with 70breastfeeding mothers with infants over 6 months of age. The method ofsampling usespurposivesampling method. The research location in the District of Gatak, Sukoharjo Regency wasconducted in December 2019. Statistical analysis was performed bivariately with the chi square test. In this study, theresults of chi square for the mother's employment status pvalue= 0.037 and husband support pvalue= 0.244.Thereis a correlationbetween mother's employment status with exclusive breastfeeding and no correlationbetweenhusband's support for exclusive breastfeeding.